Synthesis of chitin derived from shells of Philippine blue swimming crab (Portunus pelagicus) - Ongkiko, Aileen Grace Mendoza (2013)
Annually, significant amount of marine and agricultural shells are discarded from the food industry in the country and these shells contain chitin which is one of the most abundant renewable biodegradable polymer with vast applications. Accordingly, the study focused on the extraction of a biodegradable polymer from a locally-sourced shell, thereby, establishing the process for it and characterizing the generated material.The viable source of chitin was selected among the shells of blue swimming crab (Portunus pelagicus), mud crab (Scylla serrata), tiger prawn (Penaeus monodon) and golden apple snail (Pomacea canaliculata). It was found out that only shells of blue swimming crab, mud crab, and tiger prawns contain significant amount of chitin while golden apple snail has very limited, if not no chitin at all. Considering the higher availability of blue swimming crab shells from crab processing plants, this was chosen as the raw material for subsequent investigations.The kinetics study of the demineralization of chitin extraction was also conducted. The mechanism of the dissolution was investigated and was found to be limited by the product layer diffusion according to the shrinking core model. This attributed to the complex structure of the exoskeleton of the blue swimming crabs composed of proteins and calcium carbonate derivative with the latter being removed during the demineralization stage while the former is retained in the shell and serving as a product layer through which solvent has to diffuse through for continuous dissolution of the remaining mineral components. Parametric investigation was done on the extraction process using full 2k factorial design of experiment followed by an analysis of variance at 95% confidence level. It was found that high acid concentration at 2.0 N could sufficiently remove the inorganic or mineral components of the shell at room temperature while high alkaline concentration at 3.0 N applied to coarse-sized (300 µm) demineralized shells produced higher purity chitin.